2018
DOI: 10.3892/ol.2018.9212
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of trastuzumab combined with different chemotherapy regimens in multi‑line treatment of advanced human epidermal growth factor receptor 2‑positive gastric cancer: A case report

Abstract: It is generally acknowledged that gastric cancer requires comprehensive treatment approaches to be adopted. For patients with human epidermal growth factor receptor-2 (HER2)-overexpressing gastric cancer, targeting HER2 with trastuzumab in first-line therapy combined with standard chemotherapy significantly improves the prognosis. However, there is a lack of international guidance for second-line treatment if a patient experiences disease progression. There is also no accepted conclusion regarding the efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…For example, a study by Li et al. ( 121 ) showed that the use of liposomal oxaliplatin combined with apatinib, a VEGFR2 inhibitor, resulted in significant tumor growth inhibition and vascular normalization in vitro and in vivo . Similarly, Wang et al.…”
Section: Vascular Promotion Effect or Blood Vessel Normalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a study by Li et al. ( 121 ) showed that the use of liposomal oxaliplatin combined with apatinib, a VEGFR2 inhibitor, resulted in significant tumor growth inhibition and vascular normalization in vitro and in vivo . Similarly, Wang et al.…”
Section: Vascular Promotion Effect or Blood Vessel Normalizationmentioning
confidence: 99%
“…Recent studies have demonstrated the effectiveness of nanotherapy in improving blood vessel functions in HNSCC. For example, a study by Li et al (121) showed that the use of liposomal oxaliplatin combined with apatinib, a VEGFR2 inhibitor, resulted in significant tumor growth inhibition and vascular normalization in vitro and in vivo. Similarly, Wang et al (122) reported that gold nanostars with surfacemodified hyaluronic acid could selectively accumulate in HNSCC tumors and induce blood vessel normalization, which led to the enhanced efficacy of photothermal therapy.…”
Section: Vascular Promotion Effect or Blood Vessel Normalizationmentioning
confidence: 99%